Do environmentally sensitive companies engage in lesser earnings management behaviour? evidence from Malaysia - Mohd Sabrun, Ibrahim; Rusnah, Muhamad (Taylor & Francis, 2023)
Past studies have examined the influence of environmental information on earnings management practices. However, these studies have reported mixed findings and failed to establish a conclusive conclusion. Therefore, rather than re-examining the relationship between environmental disclosure and earnings management, this research offers a new perspective on earnings management based on a company’s sector, specifically, environmentally sensitive (ES) and environmentally non-sensitive (EN) sectors. This study analysed ten years of data (2008–2017) on Malaysian public listed companies. It was found that ES sectors are more likely to be involved in earnings management than EN sectors. This study’s findings could initiate policy revisions leading to sustainable, ethical and responsible financial reporting practices in the future.